2021
DOI: 10.3389/fneur.2021.613758
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Atrial Fibrillation in Stroke Patients With Patent Foramen Ovale: Systematic Review and Meta-Analysis

Abstract: Purpose: Patent foramen ovale (PFO) is associated with ischemic stroke, especially in patients with embolic stroke of undetermined source. This study aims to evaluate the presence of atrial fibrillation (AF) in ischemic stroke patients with PFO.Methods: We systematically searched EMBASE and MEDLINE databases on May 21, 2020 for studies that analyzed the presence of AF in patients with PFO. The primary outcome was the presence of AF in patients with PFO compared with those without. Outcomes were pooled using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition to our data, a recent meta-analysis found that the presence of PFO is associated with a lower risk of AF detection in patients with ischaemic stroke or TIA. 137 Another study by Yasaka et al found that risk of AF was higher in PFO patients who were older. For these reasons, in younger patients with stroke, the presence of PFO may prevent prolonged cardiac rhythm monitoring, especially when the patient has not risk factors for AF (uncontrolled hypertension or diabetes, congestive heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to our data, a recent meta-analysis found that the presence of PFO is associated with a lower risk of AF detection in patients with ischaemic stroke or TIA. 137 Another study by Yasaka et al found that risk of AF was higher in PFO patients who were older. For these reasons, in younger patients with stroke, the presence of PFO may prevent prolonged cardiac rhythm monitoring, especially when the patient has not risk factors for AF (uncontrolled hypertension or diabetes, congestive heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, there was no significant difference in the incidence of AF between patients with PFO or any IAS abnormalities compared to those without IAS abnormalities. In a recent systematic review and meta-analysis, a lower incidence of AF in patients with PFO compared with those without (RR 0.52, p < 0.001) was reported [ 40 ]. In addition, Ahmed et al [ 41 ] showed a lower incidence of AF among PFO patients, which significantly increased after PFO device closure (RR 4.68, p < 0.001) [ 42 ].…”
Section: Pfo and Afmentioning
confidence: 99%
“…The presence of a PFO is associated with a lower AF detection rate. In a meta-analysis 26 of 14 studies (13,245 patients, mean age 61.2 years), the rate of AF detection was halved in patients with PFO (relative risk (RR) = 0.52, 95% confidence interval (CI) = 0.41-0.63). The rate of AF detection was lower in patients with PFOs found on transthoracic versus transesophageal echocardiography, suggesting that the yield of AF monitoring is further reduced with increasing PFO size.…”
Section: Findings From Af Detection Studies In Cs Patientsmentioning
confidence: 99%